2020
DOI: 10.3390/ijerph17134697
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Work-Related Events and Changes in Psychological Distress and Life Satisfaction amongst Young Workers in Spain: A Gender Analysis

Abstract: A relentless stream of social, technological, and economic changes have impacted the workplace, affecting young people in particular. Such changes can be a major source of stress and can cause a threat to health and well-being. The aim of this paper is to understand the importance of work-related events and changes in the psychological distress and life satisfaction of young workers in Spain. A transversal study was carried out on a sample comprising 509 men and 396 women aged between 26 and 35 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
0
11
0
2
Order By: Relevance
“…Life satisfaction refers to the feeling of well-being with oneself in one’s surroundings (Cobos-Sanchiz et al 2020 ). In their study among 509 men and 396 women of Spain, they found that men experience higher psychological distress and reduced life satisfaction with a larger number of work-related events and changes as compared to the women.…”
Section: Research Model and Hypothesis Developmentmentioning
confidence: 99%
“…Life satisfaction refers to the feeling of well-being with oneself in one’s surroundings (Cobos-Sanchiz et al 2020 ). In their study among 509 men and 396 women of Spain, they found that men experience higher psychological distress and reduced life satisfaction with a larger number of work-related events and changes as compared to the women.…”
Section: Research Model and Hypothesis Developmentmentioning
confidence: 99%
“…Studies have demonstrated that life satisfaction is positively related to self-esteem (Cobos-Sanchiz et al, 2020;Saad, 2020), social self-efficacy (Bakioglu & Turkum, 2017;Ditchman et al, 2017;Jeon, 2016;Jian et al, 2018;Zamani & Shirazi, 2020), perceived social support (Cobos-Sanchiz et al, 2020;Malinauskas, 2010), optimism (Oriol et al, 2020;Türküm, 2005), self-control, and positive affection (Oriol et al, 2020). On the other hand, there are negative correlations between life satisfaction and psychological distress (Cobos-Sanchiz et al, 2020;Satici et al, 2020;Zhang et al, 2020), loneliness (Bakioglu & Turkum, 2017;Mellor et al, 2008), impulsivity, problematic video gaming (Cudo et al, 2020), and negative affectation (Deniz et al, 2012). Studies have shown that as individuals' social self-efficacy increases (starting and maintaining social relationships, etc.…”
Section: Satisfaction With Lifementioning
confidence: 99%
“…These results force us to consider the role of psychological distress and workload as contributors to life satisfaction, as it was highlighted by some authors in studies on life satisfaction and psychological distress (Bustamante, Bustamante, González & Bustamante, 2016;Cobos-Sanchiz et al, 2020). Consequently, work factors (Erdogan et al, 2012) and high work pressure are antecedents that predict life satisfaction (Bhatia & Mohsin, 2020).…”
Section: Discussionmentioning
confidence: 88%